Aging and Chronic Liver Disease - Maeso-Díaz, Raquel; Gracia-Sancho, Jordi (Seminars in Liver Disease, 2020)
Aging increases the incidence of chronic liver disease (CLD), worsens its prognosis, and represents the predominant risk factor for its development at all different stages. The hepatic sinusoid, which is fundamental for maintaining liver homeostasis, is composed by hepatocytes, liver sinusoidal endothelial cells, hepatic stellate cells, and hepatic macrophages. During CLD progression, hepatic cells suffer deregulations in their phenotype, which ultimately lead to disease development. The effects of aging on the hepatic sinusoid phenotype and function are not well understood, nevertheless, studies performed in experimental models of liver diseases and aging demonstrate alterations in all hepatic sinusoidal cells. This review provides an updated description of age-related changes in the hepatic sinusoid and discusses the implications for CLD development and treatment. Lastly, we propose aging as a novel therapeutic target to treat liver diseases and summarize the most promising therapies to prevent or improve CLD and extend healthspan.
Keywords: aging; liver sinusoid; cirrhosis; healthspan; LSEC; HSC